Effect of topical bovine colostrum in wound healing of corneal surface after acute ocular alkali burn in mice. (July 2022) - Tarff, Andreina; Drew-Bear, Laura E.; Di Meglio, Laura; Yee, Rebecca; Vizcaino, Maria Adelita; Gupta, Praveena; Annadanam, Anvesh; Cano, Marisol; Behrens, Ashley
Abstract: The purpose of this study was to evaluate the effect of bovine colostrum (BC) in the regeneration of corneal epithelial cells on an ocular alkali burn model. Twenty-four C57BL/6 mice were categorized into two gender/age-matched groups for treatment. Two days after inducing a corneal alkali burn in all left eyes with 4 μl of sodium hydroxide 0.15 mol/l, both eyes of group 1 were treated with BC 4 times per day, and both eyes of group 2 were treated with isotonic saline solution (SS). The epithelial defect was photographed and measured by fluorescein staining on days two, four, seven, and ten. Ocular burn damage was assessed with a pre-established classification in clock hours from the limbus. After 10 days both eyes were processed, half of the group's corneas were assessed histopathologically, and the other half was used for pro/anti-inflammatory cytokine quantification using ELISA. BC treated (Group 1) corneas revealed significantly improved fluorescein staining score for limbal involvement when compared to SS treated (Group 2) corneas at days 4 (p = 0.013), 7 (p < 0.001), and 10 (p < 0.001), respectively. No differences were noted in limbal involvement at day 2 between the two groups (p > 0.99). The overall change (difference in slope) in fluorescein staining for limbal involvement between days 2 and 10 was −0.1669 (p = 0.006). Histologic examinations and cytokine measurements of group 2 demonstrated a strong inflammatory component compared to group 1. Our data indicates that topical application of BC facilitates corneal re-epithelialization and wound healing by suppressing the inflammatory process in an ocular alkali burn model. Highlights: Bovine colostrum promotes corneal re-epithelialization and wound healing. Burned bovine colostrum-treated corneas showed higher levels of IL-10 and TGF-β. Burned saline solution-treated corneas exhibited strong neovascularization.